GAME‘S APPLICATION: Learning Method Using Maze Game Media to Increase the Learning Outcomes of Early Childhood Students - Dema Yulianto; Maryana; Sumarni Rumfot; Muhammad Ridhwan; Jasiah (Journal of Childhood Development, 2023)
Student learning outcomes can measure the achievement of learning objectives, so increased learning outcomes can also determine the success of a lesson. Efforts to improve student learning outcomes can be made by implementing Classroom Action Research (CAR). Providing action in the form of a game-based learning approach using maze game media in classes where the learning process tends to be monotonous has the potential to be a solution to improving student learning outcomes. This action was carried out on class II students who had problems with low student learning outcomes. At the pre-cycle stage, the average grade II grade was only 51.6, and the classical completeness was only 40%. The action in applying a game-based learning approach using maze game media given to class II succeeded in increasing student learning outcomes in each cycle. In the first cycle, the average score was 68.3 and the classical learning mastery was 65.2%; in the second cycle, the average value was 78.3 and the classical learning mastery was 82.6%.